Современный политологический словарь: словарь / В.И. Даниленко - Даниленко В.И. (NOTA BENE, 2000)
Экземпляры: (20191015) / Инвентарный номер: 26903 / Цена: 170.00 / Сис.шифр: 66.01 / Авт.знак: Д18 / ГРНТИ: 11.01.33 / ББК: 66.01 я21